Decoding PARP roles in breast cancer therapy resistance - Mohammad Abohassan; Farag M. Altalbawy; Majid S. Jabir; Thikra F. Hasan; Ashishkumar Kyada; Deepak Nathiya; Parjinder Kaur; M. Ravi Kumar; Munthar Kadhim Abosaoda; Muhammad Shahid Iqbal (Molecular Biology Reports, 2026)

Genome sequencing reveals genes under selection for olfactory transduction in highland sheep - Anees Ahmad; Muhammad Ibrahim; Muhammad Yaqoob; Muhammad Fahim; Sher Hayat Khan; Israr Ud Din; Majid Khan; Sohail Ahmad (Molecular Genetics and Genomics, 2026)
Kutta is an indigenous sheep breed found in the mountainous region of Swat, Pakistan. In this study we evaluated the performance of Kutta sheep within their natural habitat and identified genomic regions associated with environmental adaptability using whole genome sequencing. Flocks are mostly managed under a transhumant production system with year-round breeding. Kutta sheep demonstrated higher lambing efficiency under the available resources. Although the body size of rams and ewes was comparable, significant variation was observed among different age groups. Whole genome sequencing identified 15.46 million variants relative to Oar_v1.0 reference genome assembly. Exonic variants accounted for 2.3% of all protein coding gene variants and affected 6347 genes. These genes were primarily enriched in pathways related to G protein-coupled receptor signaling (700 genes) and olfactory transduction (500 genes). Selective sweep analysis detected 1930 genes within the regions of high homozygosity across the genome. Based on homozygosity patterns, biological relevance, and colocalization with known QTLs, 11 candidate genes were identified as putative selective signature. Five of these genes (OR4C6L, OR1086L, OR5AK2L, QR5T2L, OR9Q2) belonged to the olfactory receptor family. These olfactory receptor genes may contribute to high-altitude adaptation in Kutta sheep by enhancing their ability to locate food resources, recognize mates, and detect predators in challenging mountainous environments. Further screening of the OR4C6L sequence across 12 indigenous sheep breeds revealed marked differences between highland and lowland populations. Collectively, these findings provide comprehensive genomic insights into high-altitude adaptation of sheep and highlight the potential role of olfactory perception in survival and environmental fitness.

Phytochemical-rich extract of Psidium guajava ameliorates letrozole-induced PCOS in female rats by modulating the NF-κB inflammatory pathway - Hao Xu; Palwasha Haider; Majid Manzoor; Rida Siddique; Hina Manzoor; Muhammad Yasir Ali; Rizwan Rashid Bazmi; Liaqat Hussain; Ping Wang (Tissue and Cell, 2026)

Advanced biopolymer/metal-organic framework nanocomposites for broad-spectrum contaminant immobilization: A multi-scale computational investigation - Rouyan Farhadniya; Mahdi Golriz; Azita Jahanian; Eiman Alibakhshi; Iman Salahshoori; Majid Namayandeh Jorabchi; Ardeshir Saeidi; Kasim Sakran Abass; Muhammad Naqvi; Hossein Ali Khonakdar (Journal of Environmental Chemical Engineering, 2026)

Nickel deposits and occurrences in Africa: Distribution, geological characteristics, resource potential and associated critical minerals - Cynthia Fataki Fatuma; Muhammad Ouabid; Etienne Kadima Kabongo; Otmane Raji; Majid El Baroudi; Mostafa Benzaazoua; Abdellah Mouttaqi (Journal of African Earth Sciences, 2026)

Recent advances in electrochemical ion separation: Materials, mechanisms and sustainable applications for water and resource recovery - Luqman Ali; Abdul Majid Khan; Muhammad Usman Hameed; Saleem Raza; Liguo Shen; Imran Shakir; Muhammad Hafeez (Desalination, 2026)

Growth dynamics and disease resistance of cluster beans were associated with antioxidant enzymes feedback against soil rhizospheric pathogens - Muhammad Waseem Abbasi; Sabina Parveen; Ishrat Jahan; Qu Wei; Marium Tariq; Muhammad Azeem; Mubashar Raza; Muhammad Javed Zaki; Majid Sharifi-Rad (Acta Physiologiae Plantarum, 2026)

Regional Temperature Trends and Future Warming Risks in Pakistan Using Bias‐Corrected CMIP6 Ensembles and Machine Learning Techniques - Hamd Ullah; Firdos Khan; Majid Khan; Muhammad Abbas (International Journal of Climatology, 2026)
Pakistan faces climate‐related hazards such as floods, droughts, and heatwaves, driven by diverse climate and rising temperatures. Reliable predictions are crucial for water management, agriculture, and disaster response, but the country's complex terrain requires region‐specific assessments. This study improves regional temperature projections by integrating ensembling techniques, statistical bias correction, and machine learning algorithms. Fuzzy C‐Means clustering divided Pakistan into six climatically similar regions. CMIP6 model outputs were evaluated and bias‐corrected to reduce errors. Temperature trends were estimated using both Sen's slope estimator and Random Forest regression (RFR). Sen's slope identified steady warming trends, while RFR captured nonlinear changes more effectively. Future projections under the SSP2‐4.5 and SSP5‐8.5 scenarios for three periods (2015–2044, 2045–2074, and 2075–2100) show significant warming, especially in central and southern Pakistan. Spatial analysis shows that warming increases relative to the baseline, notably under SSP5‐8.5, with larger increases in lowland and southern areas. The SSP2‐4.5 scenario suggests partial stabilisation toward the end of the century, while the SSP5‐8.5 scenario predicts accelerated warming that threatens food security, water resources, and public health. Bias correction reduces systematic deviations between modelled and observed data, but uncertainties persist under non‐stationary climate conditions. The framework improves regional analysis, yet uncertainties arising from bias‐correction assumptions and model limitations should be considered when interpreting results. By integrating these techniques, the study fills a gap in Pakistan's climate research, offering localised insights into future warming and valuable guidance for climate adaptation and policymaking.

Ti-MOF anchored polyaniline network on separator: A dual-function strategy for polysulfide immobilization and redox enhancement in Li-S batteries - Abdul Majid Khan; Yasir Shah; Fakhar Zaman; Rashida Yahya; Safdar Abbas; Dianfa Zhao; Muhammad Usman Hameed; Wei Liu; Teng Zhang; Zhanpeng Wu (Fuel, 2026)

Heat stress associated depression and allied affliction: Therapeutic roles of nutrition, micronutrients, and phytochemicals-a review - Taha Majid Mahmood Sheikh; Abdul Malik Tareen; Muhammad Asif Arain (International Journal of Biometeorology, 2026)

Data-driven modelling of coastal water quality dynamics - Muhammad Uzair Mahmood; Man Sing Wong; Majid Nazeer; Sawaid Abbas; Alessandro Stocchino; Ken Tse Man Wong (Frontiers in Marine Science, 2026)
Long-term coastal monitoring networks provide the opportunity to evaluate how water-quality predictability varies across contrasting coastal bays. However, most machine learning studies focused on individual stations, optically active variables or short validation periods. We analyze 37 years (1986-2023) of monthly in-situ data from 94 stations across four Hong Kong Bay systems Central Harbours, Eastern Bays, Southern Bays, and Western Bays to test whether empirical predictability and highest-ranked water-quality predictors vary systematically with regional hydrography. Eight parameters: ammonia, nitrate, and nitrite nitrogen; dissolved oxygen; pH; salinity; temperature; and chlorophyll-a were assessed. Five machine-learning models Random Forest (RF), Gradient Boosting (GB), XGBoost (XGB), Support Vector Machine (SVM), and Artificial Neural Network (ANN) were evaluated under chronological 70/30 split with Bayesian-optimised hyperparameters. Tree-based ensembles produced the most stable performance overall, with strong performance for temperature and salinity, moderate-to-variable performance for selected nutrient species, and weak transferability for dissolved oxygen and pH. Chlorophyll-a remained among the least predictable variables across most bay systems under the chronological validation framework. SHAP analysis revealed regional transition in predictor structure: salinity, temperature and dissolved oxygen dominated mixing-structured Central, Eastern and Southern systems, while nitrate and ammonia became more important in Pearl River-influenced Western Bays. Long-term analyses indicated a declining pH trend in the urbanised Central Harbours and Southern and Western Bays, whereas Eastern Bays remained comparatively stable. These findings provide regional benchmark for empirical water-quality predictability under chronological validation and identify the need to incorporate lagged hydrometeorological, watershed and discharge variables for future forecasting applications.

Genomic characterization of an isolate of tomato leaf curl New Delhi virus associated with tomato crops - Abdul Majid; Muhammad Taimoor Shakeel; Muhammad Naveed Aslam; Ambreen Maqsood; Muhammad Raheel; Waqas Ashraf; Tahir Farooq; Atta ur Rehman Khan; Mahmoud Ahmed Amer; Mohammed Ali Al-Saleh (European Journal of Plant Pathology, 2026)

Correction: Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2026)

Advances in functional carbon composites for electrochemical energy conversion and catalysis: Design strategies, mechanisms and future prospects - Luqman Ali; Muhammad Usman Hameed; Xingfen Huang; Saleem Raza; Abdul Majid Khan; Mashkoor Ahmad; Akif Safeen; Imran Shakir (Journal of Environmental Chemical Engineering, 2026)

Synergistic Degradation and Cytotoxicity Mitigation of Meloxicam Using UV/Perovskite/H₂O₂ and Gamma/H₂O₂: A Comparative Study - Muhammad Asad Khan; Mohamed A. Habib; Muhammad Imran Kanjal; Majid Muneer; Muhammad Asghar Jamal; Tanveer Hussain Bokhari; Usman Irshad; Ahmed B. M. Ibrahim (Water, Air, & Soil Pollution, 2026)

Multidrug-resistant Staphylococcus aureus robustly activates the complement system but resists downstream effector mechanisms - Muhammad Naveed; Sadia Akbar; Isfahan Tauseef; Abdul Majid; Fazal Ullah; Kashif Syed Haleem (Archives of Microbiology, 2026)

Assessing food waste metrics and interventions in the Malaysian food service industry: A systematic literature - Aliffaizi Arsat; Muhammad Izzat Zulkifly; Mohd Aliff Abdul Majid; Mohd Salehuddin Mohd Zahari (Journal of Environmental Management, 2026)

Unraveling oak diversity: molecular characterization and phylogenetic relationships of Quercus species from the western Himalayas - Ayesha Azeem; Daniel Potter; Abdul Majid; Sajjad Sajjad; Khushi Muhammad; Irfan Ullah; Asif Khan; Abdulwahed Fahad Alrefaei; Sajid Ali (Plant Systematics and Evolution, 2026)

A Comprehensive Study on Radiation-Assisted Detoxification of Hazardous Industrial Effluents: A Statistical Approach - Saif Ullah; Mohamed A. Habib; Majid Muneer; Muhammad Imran Kanjal; Gulraiz Ahmad; Ahmed B. M. Ibrahim; Rana Muhammad Zulqarnain; Lotfi Mouni (Water, Air, & Soil Pollution, 2026)

Climate-driven Modifications in Structural and Functional Traits of Couch Grass [Cynodon Dactylon (L.) Pers.] along Elevation Gradient - Sana Fatima; Farooq Ahmad; Zahida Parveen; Sana Basharat; Mansoor Hameed; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Syed Mohsan Raza Shah; Raza Shah; Muhammad Ashraf; Muhammad Kaleem; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Synthesis of silver nanoparticles using vegetable waste, possible toxicities, and oxidative stress biomarker in Cyprinus carpio - Huma Ayub; Qaisar Khan; Umar Ijaz; Muhammad Asif Gondal; Raja Majid Khurshid (Fish Physiology and Biochemistry, 2026)

Ecological Insights into Plant Diversity and Distribution Along Environmental Gradients in Haveli Kahuta, Pakistan - Syed Tahir Hussain Bukhari; Khawaja Shafique Ahmad; Muhammad Tayyib Riaz; Majid Mahmood Tahir; Ansar Mehmood; Ummar Iqbal; Tajmal Imtiaz; Hazem M. Kalaji; Manzer H. Siddiqui (Environmental Monitoring and Assessment, 2026)

Exploring microbiological transformation of glutamate to γ-aminobutyric acid unleashed by a potential Lactobacillus spp. isolated from commercial cheese samples - Sikander Ali; Taha Shafi; Iram Liaqat; Muhammad Usman Ahmad; Ifrah Shabbir; Tariq Aziz; Maha Alharbi; Ashwag Shami; Fahad Al-Asmari; Ibrahim Faisal Halawani; Abdullah A. Alqasem; Reham M. Mashat; et al. (International Dairy Journal, 2026)

National-scale land suitability assessment for eucalyptus plantation in Pakistan using analytic hierarchy process (AHP) and geospatial modeling - Faisal Khalid; Sami Ullah; Muhammad Shafique; Majid Hussain (Forest Ecology and Management, 2026)

Ardisiacrispin B, a natural triterpenoid saponins, suppresses dextran sulfate sodium-induced inflammatory bowel disease by rebalancing the gut microbiota and Th17/Treg of mice - Yongdui Ruan; Yitong Chen; Weijie Peng; Yuting Duan; Qing Luo; Hidayat Ullah; Muhammad Majid; Hoi Leong Xavier Wong; Yanfeng Xie; Weibo Dai; Xianjing Hu (Inflammopharmacology, 2026)

Bioprospecting Artemisia roxburghiana Wall. ex Besser extracts for their potential antimicrobial, antiprotozoal, antidiabetic and anticancer potential - Syeda Masooma Ali; Sara- Tun-Nisa; Muhammad Majid; Humaira Fatima; Ihsan- ul-Haq (Natural Product Research, 2025)

Assessment of soil biological quality under long-term rice-wheat cropping system: Effect of continuous vs. residual organic nutrient inputs - Loitongbam Joymati Chanu; Tapan Jyoti Purakayastha; Debarati Bhaduri; Muhammad Fraz Ali; Yashbir S. Shivay; Samapti Saren; Vikas Kumar; Majid Alhomrani; Abdulhakeem S. Alamri (Soil and Tillage Research, 2025)

Transformation of wet chemically derived ZnGa-LDH to ZnO:GaN nano-alloys for PMS activated wastewater remediation - Yasir Abbas; Kanwal Shabbir; Haider Aziz; Ijaz Hussain; Hafiz M. Adeel Sharif; Muhammad Ahsan Iqbal; Majid Basharat; Haoliang Wang; Niaz Ali Khan (Journal of Environmental Chemical Engineering, 2025)

Cyclotriphosphazene-derived oxygen-rich N, P-codoped carbon nanosheets for high-performance supercapacitor electrodes - Abdul Majid Khan; Muhammad Waqar Hameed; Dianfa Zhao; Muhammad Usman Hameed; Wei Liu; Teng Zhang; Zhanpeng Wu (Fuel, 2025)

Halotolerant Bacillus Aryabhattai Strain PM34 Mitigates Salinity Stress and Enhances the Physiology and Growth of Maize - Muhammad Atif Azeem; Salman Khan; Fawad Ali; Sajjad Ahmad; Gul Rahim; Muhammad Iftikhar; Majid Iqbal; Rawa Saad Aljaloud; Khaloud Mohammed Alarjani; Hassan Javed Chaudhary (Journal of Plant Growth Regulation, 2025)

Unraveling key genes and pathways involved in Verticillium wilt resistance by integrative GWAS and transcriptomic approaches in Upland cotton - Majid Khan; Daowu Hu; Shuai Dai; Hongge Li; Zhen Peng; Shoupu He; Muhammad Awais; Xiongming Du; Xiaoli Geng (Functional & Integrative Genomics, 2025)

A hybrid 3D CNN-LSTM model with soft spatial attention mechanism for accurate hyperspectral image classification - Mohamed Sultan Mohamed Ali; Md Sakib Bin Islam; Molla E. Majid; Saad Bin Abul Kashem; Amith Khandakar; Muhammad E.H. Chowdhury (Remote Sensing Applications: Society and Environment, 2025)

Analyzing the double-chain deoxyribonucleic acid model: bifurcation, chaos, and sensitivity insights through advanced analytical techniques - Sadique Rehman; Aamir Farooq; H. W. A. Riaz; Kamran Ullah Khan; Majid Hussain Shah; Muhammad Ramzan (Theory in Biosciences, 2025)

DFT investigation of pristine and li-functionalized TiS2 monolayers for toxic gas sensing applications - Zunaira Saleem; Saleh S. Alarfaji; Humaira Shaheen; Abdul Majid; Muhammad Isa Khan (Journal of Environmental Chemical Engineering, 2025)

Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2025)

Review on crack detection in civil infrastructure using structural health monitoring and machine learning techniques - Muhammad Zeeshan Khan; Maryam Shahzadi; Asim Khan; Umar Ali; Muhammad Arshad Shehzad Hassan; Majid Hussain (Innovative Infrastructure Solutions, 2025)

UV radiation-induced degradation of moxifloxacin: toxicity evaluation and conditions optimization - Muhammad Imran Kanjal; Majid Muneer; Saif Ullah; Saira Sabir; Reguia Boudraa; Abdeltif Amrane; Lotfi Mouni (Euro-Mediterranean Journal for Environmental Integration, 2025)

Rapid and selective E-waste gold extraction from aqua regia by dual redox active-sites of skeleton modulated poly(organo)phosphazenes - Yasir Abbas; Sajjad Ali; Majid Basharat; Hafiz M. Adeel Sharif; Muhammad Ahsan Iqbal; Mohamed Bououdina; Haoliang Wang; Niaz Ali Khan (Chemical Engineering Journal, 2025)

Dietary zinc requirement of Catla (Catla catla) juveniles - Anam Zafar; Syed Zakir Hussain Shah; Mahroze Fatima; Syed Makhdoom Hussain; Muhammad Mudassar Shahzad; Majid Hussain; Wazir Ali (Aquaculture International, 2025)

Fluoride contamination in plum and peach orchards and its impact on earthworm growth and reproduction - Muhammad Nauman Ahmad; Shah Saud; Afia Zia; Muhammad Baseer Us Salam; Somaira Bibi; Ayaz AlI Khan; Tariq Aziz; Saleh A. Alghamdi; Abdulhakeem S. Alamri; Majid Alhomrani (Environmental Monitoring and Assessment, 2025)

Exploring the synergies between natural resources, technological innovation, and fiscal and monetary policies for promoting environmental sustainability in ASEAN countries - Muhammad Azam Khan; Salma Zahir; Nor Salwati Othman; Abdul Majid Awan (Environment, Development and Sustainability, 2025)

PFAS insights: A review of historical data, environmental applications, health effects, and pollution challenges in Pakistan - Amna Chaudhary; Waqas Bashir; Abdul Majid; Muhammad Qasim; Erum Bughio; Minahal Fatima; Siraj U Din (Environmental Science & Policy, 2025)

Correction: Development of prediction models for strength properties of concrete using gene expression programming - Asad Ullah Khan; Muhammad Faisal Javed; Majid Khan (Innovative Infrastructure Solutions, 2025)

Insights into Wild Medicinal Plants: Assessing Mineral Profiles in the Ojhor Valley, Chitral, Pakistan - Muhammad Nauman Khan; Barkat Ullah; Alevcan Kaplan; Abdul Razzaq; Ghulam Jelani; Sana Wahab; Syed Nasar Shah; Nazima Wahid; Muhammad Adnan; Mohamed Farouk Elsadek; M. Ajmal Ali; Majid Iqbal (Biological Trace Element Research, 2025)

Flood characteristics and risk analysis in small watersheds on the Loess Plateau under extreme heavy rainfall - Muhammad Imran; Jingming Hou; Tian Wang; Qingshi Zhou; Donglai Li; Majid Habib Khan; Irfan Ullah; Rana Shahzad Noor; Muhammad Umair; Shakeel Hussain (Natural Hazards, 2025)

Eco-friendly herbicide tolerance in maize (Zea mays Linn.) using moringa (Moringa oleifera Lam.) leaf extract - Hameed Ullah Khan; Muhammad Mudasar Aslam; Tahir Iqbal; Amana Khatoon; Muhammad Jamil; Shafiq Ur Rehman; Muhammad Nauman Khan; Majid Iqbal; Alevcan Kaplan; Sarah Abdul Razak; Baber Ali; Muhammad Siddique Afridi; et al. (Acta Physiologiae Plantarum, 2025)

In vitro, in silico anti-tyrosinase and anti-inflammatory activity elucidation of chrysophanol isolated from Platycladus orientalis (L.) Franco - Muhammad Rafiq; Abdul-Rehman Phull; Mubashir Hassan; Abdul Majid; Song-Ja Kim (Next Research, 2025)

Multi-model assessment of climate change impacts on drought characteristics - Adnan Dehghani; Fatemehsadat Mortazavizadeh; Amin Dehghani; Muhammad Bin Rahmat; Hadi Galavi; David Bolonio; Jing Lin Ng; Vahid Rezaverdinejad; Majid Mirzaei (Natural Hazards, 2025)

Correction: Comparative Effect of a Feedstock and its Biochar on Soil Biochemical Properties under Low and Optimum Moisture Availability in C Poor and C Rich Soils - Zubda Zahid; Tanvir Shahzad; Muhammad Sanaullah; Hayssam M. Ali; Abdul Majid; Jiřina Száková (Journal of Soil Science and Plant Nutrition, 2025)

Comparative Effect of a Feedstock and its Biochar on Soil Biochemical Properties Under Low and Optimum Moisture Availability in C Poor and C Rich Soils - Zubda Zahid; Tanvir Shahzad; Muhammad Sanaullah; Hayssam M. Ali; Abdul Majid; Jiřina Száková (Journal of Soil Science and Plant Nutrition, 2025)

Development of prediction models for strength properties of concrete using gene expression programming - Asad Ullah Khan; Muhammad Faisal Javed; Majid Khan (Innovative Infrastructure Solutions, 2025)

ECCDN-Net: A deep learning-based technique for efficient organic and recyclable waste classification - Md. Sakib Bin Islam; Md. Shaheenur Islam Sumon; Molla E. Majid; Saad Bin Abul Kashem; Mohammad Nashbat; Azad Ashraf; Amith Khandakar; Ali K. Ansaruddin Kunju; Mazhar Hasan-Zia; Muhammad E.H. Chowdhury (Waste Management, 2025)

Novel mutations in exon 2 of follistatin (FST) gene associated with wool fiber diameter in sheep - Tahira Mir; Muhammad Ibrahim; Muhammad Siraj; Sajid Ali Khan Bangash; Sher Hayat Khan; Majid Khan; Muhammad Tayyab; Sohail Ahmad (Small Ruminant Research, 2025)

Spore morphometric analysis in Sino-Himalayan and W-Himalayan Athyriaceae taxa: taxonomic insights and molecular phylogenetic comparison - Syed Nasar Shah; Mushtaq Ahmad; Mohammad Javed Ansari; Muhammad Nauman Khan; Majid Iqbal; Baber Ali; Sami Al Obaid (Genetic Resources and Crop Evolution, 2025)

Thermokinetic investigation of Polyethylene Terephthalate (PET) plastic over biomass fly ash (BFA) catalyst using pyrolysis process through non-isothermal thermogravimetric analysis - Ali Raza; Waqar Ul Habib Khan; Asif Hussain Khoja; Arslan Khan; Muhammad Hassan; Rabia Liaquat; Majid Ali; Israf Ud Din; Abdulaziz Al-Anazi (Sustainable Chemistry and Pharmacy, 2024)

Leveraging machine learning to model salinity and water flux for improved insights into forward osmosis membrane bioreactors - Ali Aldrees; Bilal Siddiq; Wael S. Al-Rashed; Muhammad Faisal Javed; Majid Khan (Journal of Water Process Engineering, 2024)

Efficient removal of perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) from aqueous solution using modified biochar: Preparation, performance, and mechanistic insights - Waqas Niaz; Dahai Zhang; Zia Ahmad; Nan Shen; Waqas Haider; Imran Ali; Muhammad Usman; Abdul Majid; Sheikh Fahad Javaid; Muhammad Ahsan Amjed; Xianguo Li (Journal of Environmental Chemical Engineering, 2024)

Pre-emergence herbicide selection for successful cultivation of black seed (Nigella sativa L.), psyllium (Plantago ovata Forsk), and quinoa (Chenopodium quinoa Willd.) - Muhammad Zia Ul Haq; Saira Shafiq; Muhammad Zia Ul Mohsin; Majid Ali; Abdul Khaliq; Rana Nadeem Abbas; Muhammad Zafar Iqbal; Amar Matloob (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Beyond the biological prime: Deciphering the link between child survival and maternal age in India - Muhammad Farhan Majid; Opinder Kaur; Anil B. Deolalikar (Economics & Human Biology, 2024)

Overexpression of Gossypium arboreum 3-ketoacyl-CoA synthase 6 (GaKCS6) gene enhanced leaf epicuticle wax in Gossypium hirsutum L. and improved tolerance against whitefly - Muhammad Umair Majid; Rabiah Ashraf; Basit Jabbar; Usman Arif; Fatima Batool; Sameera Hassan; Bushra Rashid (Biocatalysis and Agricultural Biotechnology, 2024)

Unveiling the sweetness: evaluating yield and quality attributes of early generation sweet corn (Zea mays subsp. sachharata) inbred lines through morphological, biochemical and marker-based approaches - Shah Mohammad Usman; Raheel Shafeeq Khan; Asif Bashir Shikari; Nida Yousuf; Showkat Ahmad Waza; Shabir Hussain Wani; Muhammad Ashraf Bhat; F. Shazia; Faroq Ahmad Sheikh; Asma Majid (Molecular Biology Reports, 2024)

Assessment of Machine Learning Algorithms for Land Cover Classification in a Complex Mountainous Landscape - Gomal Amin; Iqra Imtiaz; Ehsan Haroon; Najum us Saqib; Muhammad Imran Shahzad; Majid Nazeer (Journal of Geovisualization and Spatial Analysis, 2024)
Mapping land cover (LC) in mountainous regions, such as the Gilgit-Baltistan (GB) area of Pakistan, presents significant challenges due to complex terrain, limited data availability, and accessibility constraints. This study addresses these challenges by developing a robust, data-driven approach to classify LC using high-resolution Sentinel-2 (S-2) satellite imagery from 2019 within Google Earth Engine (GEE). The research evaluated the performance of various machine learning (ML) algorithms, including classification and regression tree (CART), maximum entropy (gmoMaxEnt), minimum distance (minDistance), support vector machine (SVM), and random forest (RF), without extensive hyperparameter tuning. Additionally, ten different scenarios based on various band combinations of S-2 data were used as input for running the ML models. The LC classification was performed using 2759 sample points, with 70% for training and 30% for validation. The results indicate that the RF algorithm outperformed all other classifiers under scenario S1 (using 10 bands), achieving an overall accuracy (OA) of 0.79 and a kappa coefficient of 0.76. The final RF-based LC mapping shows the following percentage distribution: barren land (46.7%), snow cover (22.9%), glacier (7.9%), grasses (7.2%), water (4.7%), wetland (2.9%), built-up (2.7%), agriculture (1.9%), and forest (1.2%). It is suggested that the best identified RF classifier within the GEE environment should be used for advanced multi-source data image classification with hyperparameter tuning to increase OA. Additionally, it is suggested to build the capacity of various stakeholders in GB for better monitoring of LC changes and resource management using geospatial big data.

Exploring Oxyfluorfen's Environmental Fate: Soil Affinity, Persistence, Degradation Dynamics and Ecological Implications - Sara Majid; Khuram Shahzad Ahmad; Muhammad Azad Malik; Abdulnasser M. Karami (Agricultural Research, 2024)

Integrative metagenomic dissection of last-resort antibiotic resistance genes and mobile genetic elements in hospital wastewaters - Muhammad Shafiq; Xiaoling Guo; Meimei Wang; Hazrat Bilal; Li Xin; Yumeng Yuan; Fen Yao; Taha Majid Mahmood Sheikh; Muhammad Nadeem Khan; Xiaoyang Jiao (Science of The Total Environment, 2024)

Erratum to “Improved project control for sustainable development of construction sector to reduce environment risks” [J. Clean. Product. (2019) 118214] - Summaira Malik; Fareena Fatima; Asma Imran; Lai Fatt Chuah; Jirí Jaromír Klemes; Imran Hameed Khaliq; Saira Asif; Muhammad Aslam; Farrukh Jamil; Abdullah Khan Durrani; Majid Majeed Akbar; Muhammad Shahbaz; et al. (Journal of Cleaner Production, 2024)

The importance of sharing: wild plant knowledge in three valleys of Northern Pakistan - Adnan Ali Shah; Abid Raza; Naji Sulaiman; Dipak Khadka; Abdul Majid; Muhammad Abdul Aziz; Arshad Mehmood Abbasi; Mushtaq Ahmad; Andrea Pieroni (Plant Biosystems, 2024)

Analyzing policy implications by considering adoption barriers on consumer adoption intention for electric vehicles: a comprehensive overview - Farheen Ehsan; Salman Habib; Muhammad Majid Gulzar; Junhua Guo (Environment, Development and Sustainability, 2024)

From lake to fisheries: Interactive effect of climate and landuse changes hit on lake fish catch? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Majid Rasta; Caihong Hu; Chengshuai Liu; Yinghai Li; Ao li; Jijun Chen; Chunyun Zhu; Sher Ali; Jiali Guo; et al. (Environmental Research, 2024)

Optimized prediction modeling of micropollutant removal efficiency in forward osmosis membrane systems using explainable machine learning algorithms - Ali Aldrees; Muhammad Faisal Javed; Majid Khan; Bilal Siddiq (Journal of Water Process Engineering, 2024)

On the versatility of graphene-cellulose composites: An overview and bibliometric assessment - Nur Faraliana Japri; Zaiton Abdul Majid; S.K. Ghoshal; Wan Hazman Danial; Hong Heng See; Muhammad Zamir Othman (Carbohydrate Polymers, 2024)

Comparative resistance of wheat genotypes to aphid infestation under varied sowing dates - Muhammad Nawaz; Irfanullah Khan; Farman Ullah Dawar; Ibni Amin Khalil; Zahid Hussain; Jan Saad; Syed Majid Rasheed; Khan Rahamdad (Ecological Genetics and Genomics, 2024)

Berberine and RNAi-Targeting Telomerase Reverse Transcriptase (TERT) and/or Telomerase RNA Component (TERC) Caused Oxidation in Colorectal Cancer Cell Line, HCT 116: An Integrative Approach using Molecular and Metabolomic Studies - Muhammad Azizan Samad; Mohd Zuwairi Saiman; Nazia Abdul Majid; Saiful Anuar Karsani; Jamilah Syafawati Yaacob (Cell Biochemistry and Biophysics, 2024)

GCDN-Net: Garbage classifier deep neural network for recyclable urban waste management - Md Mosarrof Hossen; Azad Ashraf; Mazhar Hasan; Molla E. Majid; Mohammad Nashbat; Saad Bin Abul Kashem; Ali K. Ansaruddin Kunju; Amith Khandakar; Sakib Mahmud; Muhammad E.H. Chowdhury (Waste Management, 2024)

Development and Characterization of Glimepiride-Loaded Polymeric Nanoparticles: Formulation Design and Evaluation - Zaiba Irfan; Muhammad Imran Khan; Muhammad Farhan Sohail; Muhammad Furqan Akhtar; Muhammad Naeem Qaisar; Muhammad Kashif Javed; Fareeha Anwar; Badarqa-tul-Ayesha; Majid Anwar; Aslam Khan; Faizan Akram (Journal of Pharmaceutical Innovation, 2024)

Integration of chitosan coating and short-term hypobaric treatment extends postharvest life and upregulates defense-related enzymes in apple fruit - Syed Umair Shah; Majid S. Hashmi; Muhammad Rafiullah Khan; Ayaz Ahmad; Aysha Riaz; Yosef Al Shoffe; Said Wahab; Muhammad Ayub; Antonio Ippolito (European Journal of Plant Pathology, 2024)

Corrigendum to “Effect of exogenous application of biogenic silicon sources on growth, yield, and ionic homeostasis of maize (Zea mays L.) crops cultivated in alkaline soil” [Chemosphere 341, November (2023) 140019] - Arwa Abdulkreem AL-Huqail; Ali Rizwan; Muhammad Zia-ur-Rehman; Haifa Abdulaziz Sakit Al-Haithloul; Suliman Mohammed Suliman Alghanem; Muhammad Usman; Naveeda Majid; Yousef Alhaj Hamoud; Muhammad Rizwan; Amany H.A. Abeed (Chemosphere, 2024)

Impact of urban spatial factors on NO2 concentration based on different socio-economic restriction scenarios in U.S. cities - Muhammad Waqas; Majid Nazeer; Man Sing Wong; Wu Shaolin; Li Hon; Joon Heo (Atmospheric Environment, 2024)

Rainwater harvesting for agriculture development using multi-influence factor and fuzzy overlay techniques - Xiangtian Zheng; Abid Sarwar; Fakhrul Islam; Abdul Majid; Aqil Tariq; Muhammad Ali; Shazia Gulzar; Muhammad Ismail Khan; Muhammad Akmal Sardar Ali; Muhammad Israr; Ahsan Jamil; Muhammad Aslam; et al. (Environmental Research, 2023)

Effect of exogenous application of biogenic silicon sources on growth, yield, and ionic homeostasis of maize (Zea mays L.) crops cultivated in alkaline soil - Arwa Abdulkreem AL-Huqail; Ali Rizwan; Muhammad Zia-ur-Rehman; Haifa Abdulaziz Sakit Al-Haithloul; Suliman Mohammed Suliman Alghanem; Muhammad Usman; Naveeda Majid; Yousef Alhaj Hamoud; Muhammad Rizwan; AmanyH.A. Abeed (Chemosphere, 2023)

The impact of CO2 saturated brine temperature on wormhole generation and rock geomechanical and petrophysical properties - Abdullah Al-Dhafeeri; Murtada Saleh Aljawad; Mustafa Al Ramadan; Ahmed Farid Ibrahim; Muhammad M. Al Majid; Zuhair Al-Yousef; Ahmed Al-Yaseri (Gas Science and Engineering, 2023)

Sustainable remediation of dye-contaminated wastewater using novel cross-linked Hex-CCP-co-PPT microspheres - Sahid Mehmood; Fazal Haq; Mehwish Kiran; Ibrahim A. Shaaban; Mohammed A. Assiri; Muhammad Haroon; Muhammad Yasin; Arshad Farid; Alam Nawaz; Majid Majeed Akbar; Zeinhom M. El-Bahy (Chemosphere, 2023)

Tailoring triple charge (O2−/H+/e−) conducting nature of Fe-based lanthanum doped samarium oxides for ceramic fuel cells (CFCs) - Muhammad Yousaf; Yuzheng Lu; Majid Niaz Akhtar; Ali Sarosh Khawaja; Khalid Mujasam Batoo; Sajjad Hussain; Asma Noor; Muhammad Akbar; Hu Enyi; M.A.K Yousaf Shah; Naveed Mushtaq; Bin Zhu (Fuel, 2023)

Microbial detoxification of bifenthrin insecticide by selected fungal strains and optimizing conditions using response surface methodology for agricultural sustainability - Sara Majid; Khuram Shahzad Ahmad; Wahidah H. Al-Qahtani; Muhammad Azad Malik (Environmental Monitoring and Assessment, 2023)

The impact of climate change on agricultural productivity and agricultural loan recovery; evidence from a developing economy - Fakhrul Wahab; Majid Jamal Khan; Muhammad Yar Khan; Rukhshanda Mushtaq (Environment, Development and Sustainability, 2023)

Phytoremediation potential modulated by structural and functional traits in a saline desert halophyte Fagonia indica Burm. f - Nargis Naz; Sana Fatima; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Syed Mohsan Raza Shah; Farooq Ahmad; Majid Anwar; Sana Basharat; Ansa Asghar; Muhammad Ashraf (Environmental Science and Pollution Research, 2023)

Efficient resource utilization of the electricity distribution sector using nonparametric data envelopment analysis and influential factors - Majid Ikram; Muhammad Zahid Rafique; Kamel Si Mohammed; Rida Waheed; Diogo Ferraz (Utilities Policy, 2023)

Dramatic changes in anatomical traits of a C4 grass Chrysopogon serrulatus Trin. (Poaceae) over a 1000 m elevational gradient - Sana Fatima; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Mahwish Munir; Muhammad Ashraf; Syed Mohsan Raza Shah; Sana Basharat; Iftikhar Ahmad; Sangam Khalil (Journal of Mountain Science, 2023)

A novel three-band macroalgae detection index (TMI) for aquatic environments - Majid Nazeer; Mohammad M. M. Alsahli; Janet Elizabeth Nichol; Jiayi Pan; Weicheng Wu; Muhammad Bilal; Urooj Saeed (International Journal of Remote Sensing, 2023)

3D porous superoleophilic/hydrophobic grapefruit peel aerogel for efficient removal of emulsified-oil from water - Muhammad Imran; Ashraful Islam; Fatima Ismail; Panyue Zhang; Majid Basharat; Muhammad Ikram; Ahmed Uddin; Shah Zeb; Qadeer-Ul Hassan; Yongxiang Gao (Journal of Environmental Chemical Engineering, 2023)

Mixed micellar solubilization for procion blue MxR entrapment and optimization of necessary parameters for micellar enhanced ultrafiltration - Amnah Yusaf; Muhammad Usman; Muhammad Ibrahim; Asim Mansha; Atta ul Haq; Hafiza Fatima Rehman; Majid Ali (Chemosphere, 2023)

Effects of ash derived from livestock manure and two other treatments on soil moisture content and water infiltration rate - Fatemehsadat Mortazavizadeh; Amirali Fatahi; Keyvan Asefpour Vakilian; Paulo H. Pagliari; Artemi Cerdà; Majid Mirzaei; Xiuju Zhang; Rana Muhammad Adnan Ikram (Irrigation and Drainage, 2022)
This study investigates the effects of using livestock manure (LM), livestock manure ash (LMA) and the combination of LM with LMA (LM + LMA) on the soil moisture content and water infiltration rate of clay, clay loam and sandy loam soils. The soil moisture content and water infiltration rate were 11.60, 8.90 and 6.85% and 1.98, 1.55 and 1.62 cm h‾¹ for clay, clay loam and sandy loam soils, respectively, by the application of 15 t ha‾¹ LM. Moreover, using 15 t ha‾¹ of LMA had the most desirable effects on the soil moisture content in the clay and clay loam soils. Using this treatment, the soil moisture content and water infiltration rate were 10.85, 11.20 and 7.24% and 2.40, 1.90 and 1.75 cm h‾¹ for clay, clay loam and sandy loam soils, respectively. Promising results were obtained using 15 + 15 t ha‾¹ of LM + LMA, where the soil moisture content and water infiltration rate were 11.50, 10.20 and 8.20% and 2.80, 1.90 and 1.72 cm h‾¹ for clay, clay loam and sandy loam soils, respectively. Both LMA and its combination with LM were found to be positive strategies to achieve sustainable agricultural goals because of the increased water infiltrates (less runoff) available for the plants.

Correction to: Effect of eco‑friendly probiotics‑supplemented rapeseed meal–based diet on the performance of Catla catla fingerlings - Muhammad Mudassar Shahzad; Syed Makhdoom Hussain; Majid Hussain; Naveed Ahmad; Laraib Tahir; Kalsoom Akhtar (Environmental Science and Pollution Research, 2022)

Effect of eco-friendly probiotics-supplemented rapeseed meal–based diet on the performance of Catla catla fingerlings - Muhammad Mudassar Shahzad; Syed Makhdoom Hussain; Majid Hussain; Naveed Ahmad; Laraib Tahir; Kalsoom Akhtar (Environmental Science and Pollution Research, 2022)

Evaluating the impact of GDP per capita on environmental degradation for G-20 economies: Does N-shaped environmental Kuznets curve exist? - Abdul Majid Awan; Muhammad Azam (Environment, Development and Sustainability, 2022)

Antileishmanial Agents Co-loaded in Transfersomes with Enhanced Macrophage Uptake and Reduced Toxicity - Fatima Zahid; Sibgha Batool; Fakhar ud-Din; Zakir Ali; Muhammad Nabi; Salman Khan; Omer Salman; Gul Majid Khan (AAPS PharmSciTech, 2022)

Wind energy potential assessment using Weibull distribution with various numerical estimation methods: a case study in Mersing and Port Dickson, Malaysia - Muhammad Aslam Mohd Safari; Nurulkamal Masseran; Muhammad Hilmi Abdul Majid (Theoretical and Applied Climatology, 2022)

Temporal variation in leachate composition of a newly constructed landfill site in Lahore in context to environmental pollution and risks - Mahsoon Ashraf; Muhammad Zeshan; Sadia Hafeez; Rahib Hussain; Abdul Qadir; Muzaffar Majid; Farman Ahmad; Sajid Rashid Ahmad (Environmental Science and Pollution Research, 2022)

Feeding niche overlap between native and alien fishes in Swat River, Khyber Pakhtunkhwa, Pakistan - Amir Said; Muhammad Imran; Muhammad Tahir Waseem; Abdul Majid Khan; Noman Khalique; Ghulam Sarwar; Rana Manzoor Ahmad (Environmental Biology of Fishes, 2022)

Does economic complexity matter for environmental sustainability? Using ecological footprint as an indicator - Muhammad Zahid Rafique; Abdul Majeed Nadeem; Wanjun Xia; Majid Ikram; Hafiz Muhammad Shoaib; Umer Shahzad (Environment, Development and Sustainability, 2022)

Estimation of a trend of meteorological and hydrological drought over Qinhuai River Basin - Mohammad Ilyas Abro; Ehsan Elahi; Ram Chand; Dehua Zhu; Jan Muhammad; Muhammad Rafique Daudpoto; Abdul Majid Soomro; Murad Ali Khaskheli (Theoretical and Applied Climatology, 2022)

Photocatalysis: an effective tool for photodegradation of dyes—a review - Muhammad Saeed; Majid Muneer; Atta ul Haq; Nadia Akram (Environmental Science and Pollution Research, 2022)

Synthesis and characterization of ZnO decorated reduced graphene oxide (ZnO-rGO) and evaluation of its photocatalytic activity toward photodegradation of methylene blue - Asif Nisar; Muhammad Saeed; Majid Muneer; Muhammad Usman; Iltaf Khan (Environmental Science and Pollution Research, 2022)

In vitro α-glycosidase and urease enzyme inhibition profile of some selected medicinal plants of Pakistan - Abdur Rauf; Saud Bawazeer; Muhammad Naseer; Fahad A. Alhumaydhi; Abdullah S. M. Aljohani; Aamir Habib; Raheem Khan; Urooj Jehan; Muhammad Nasimullah Qureshi; Majid Khan; Umar Farooq; Amirzhan Kassenov; et al. (Natural Product Research, 2021)

Quest for Novel Preventive and Therapeutic Options Against Multidrug-Resistant Pseudomonas aeruginosa - Sidra Irum; Saadia Andleeb; Amjad Ali; Muhammad Ibrahim Rashid; Mahnoor Majid (International Journal of Peptide Research and Therapeutics, 2021)

Exogenous melatonin regulates chromium stress-induced feedback inhibition of photosynthesis and antioxidative protection in Brassica napus cultivars - Ahsan Ayyaz; Muhammad Ahsan Farooq; Muhammad Dawood; Abdul Majid; Muhammad Javed; Habib‐ur‐Rehman Athar; Hussan Bano; Zafar Ullah Zafar (Plant Cell Reports, 2021)

Outer Membrane Protein‐Coated Nanoparticles as Antibacterial Vaccine Candidates - Majid Anwar; Faqir Muhammad; Bushra Akhtar; Muhammad Irfan Anwar; Ahmad Raza; Abdul Aleem (International Journal of Peptide Research and Therapeutics, 2021)

Immunoinformatics Driven Prediction of Multiepitopic Vaccine Against Klebsiella pneumoniae and Mycobacterium tuberculosis Coinfection and Its Validation via In Silico Expression - Sidra Rahmat Ullah; Mahnoor Majid; Muhammad Ibrahim Rashid; Khalid Mehmood; Saadia Andleeb (International Journal of Peptide Research and Therapeutics, 2021)

Correction to: Biomonitoring of Toxic Metals in Feathers of Birds from North-Eastern Pakistan - Bushra Rashid; Muhammad Zubair; Nausheen Irshad; Khawaja Shafique Ahmad; Majid Mahmood; Majid Mahmood Tahir; Khizar Hussain Shah; Aqeela Shaheen (Bulletin of Environmental Contamination and Toxicology, 2021)

Biomonitoring of Toxic Metals in Feathers of Birds from North-Eastern Pakistan - Bushra Aziz; Muhammad Zubair; Nausheen Irshad; Khawaja Shafique Ahmad; Majid Mahmood; Majid Mahmood Tahir; Khizar Hussain Shah; Aqeela Shaheen (Bulletin of Environmental Contamination and Toxicology, 2021)
The current study was designed to determine the concentrations of toxic metals (Ni, Pb and Cr) in feathers of birds collected from four regions of NE Pakistan. Feather samples of birds (House Crow, Common Myna and House Sparrow) were collected from different areas. Atomic absorption spectrophotometer was used to determine the concentration of metals in feathers. Analysis of the data revealed that concentrations of Pb and Cr were significantly different ( p < 0.05) among bird species, whereas no difference ( p > 0.05) was detected among bird species (house crow, common myna and house sparrow) for Ni. A significant difference was found for the concentration of Pb and Ni in all the four studied regions. Whereas, non-significant difference was found in all the studied regions for the concentrating of Cr. It was revealed that there is significant rising concentration of metals (Pb, Cr) in feathers of birds in Azad Kashmir.

Biallelic loss-of-function variants in NEMF cause central nervous system impairment and axonal polyneuropathy - Ashfaque Ahmed; Meng Wang; Gaber Bergant; Reza Maroofian; Rongjuan Zhao; Majid Alfadhel; Marwan Nashabat; Muhammad Talal AlRifai; Wafaa Eyaid; Abdulrahman Alswaid; Christian Beetz; Yan Qin; et al. (Human Genetics, 2021)

Remote Sensing of Narrowing Barrier Islands along the Coast of Pakistan over Past 30 Years - Shamsa Kanwal; Xiaoli Ding; Muhammad Sajjad; Majid Nazeer; Ibrahim Zia (Journal of Marine Science and Engineering, 2021)
Barrier islands (BIs) are the first line of defense against the sea/wave actions in coastal areas, and assessing their stability is crucial in the context of effective coastal planning. Therefore, this study evaluates the spatial–temporal shoreline changes of the BIs in Pakistan over the past three decades (1989–2018). Satellite data from Landsat missions are used to delineate the shorelines of 19 BIs in Pakistan. After delineating the shorelines from satellite observations, two well-known statistical methods (i.e., end point rate (EPR) and linear regression rate (LRR)) are used to capture the localized changes in the BIs. The results ascertain that nearly all of the BIs have experienced noteworthy erosion during the past three decades. While the mean erosion over all the BIs during the study period is estimated to be >6 m/y, significant spatial heterogeneities among the individual BIs exist. The interdecadal comparison indicates that the highest mean erosion of the BIs occurred during the period 1989–1999 (13.03 ± 0.62 m/y), which gradually reduced over the preceding decades (i.e., 7.76 ± 0.62 m/y during the period 1999–2009 and 3.8 ± 0.7 m/y during the period 2009–2018). Nevertheless, ~65% of the total BIs experienced high erosion (>2 m/y), ~15% experienced moderate (

Exploring the role of fossil fuels, hydroelectricity consumption, and financial sector in ensuring sustainable economic development in the emerging economy - Faisal Faisal; Muhammad Numan Khan; Ruqiya Pervaiz; Peshraw Majid Muhamad; Mohammad Othman Jamil Rashdan (Environmental Science and Pollution Research, 2021)

Study on the dissipation pattern and risk assessment of metalaxyl-M in rice grains and paddy soil and water by liquid chromatography-tandem mass spectrometry - Yahui He; Xu Jiao; Tangwei Zhang; Mengqiang Wang; Majid Khan; Muhammad Rafiullah Khan; Yongxin She (Environmental Science and Pollution Research, 2021)

Systematic study of the new remains of Propotamochoerus hysudricus (Suidae, Mammalia) from the Late Miocene–Early Pliocene of Middle Siwaliks (Pakistan) - Sadaf Aslam; Abdul Majid Khan; Rana Manzoor Ahmad; Ayesha Iqbal; Muhammad Tahir Waseem (Arabian Journal of Geosciences, 2021)

Does globalization and financial sector development affect environmental quality? A panel data investigation for the Middle East and North African countries - Abdul Majid Awan; Muhammad Azam; Imran Ullah Saeed; Baher Bakhtyar (Environmental Science and Pollution Research, 2020)

Telomerase reverse transcriptase downregulation by RNA interference modulates endoplasmic reticulum stress and mitochondrial energy production - Muhammad Zuhair Mohd Zain; Nor Hayati Ismail; Nadhirah Ahmad; Sarina Sulong; Saiful Anuar Karsani; Nazia Abdul Majid (Molecular Biology Reports, 2020)

Anti-urease and cytotoxic activity of 1-Nitro-2-phenylethane and Nerolidol; two major compounds isolated from the seeds of Dennettia tripetala - Samuel E. Ugheighele; Kate E. Imafidon; Muhammad I. Choudhary; Ahmed Shakil; Majid Khan; Zaid A. Sherwani; Zaheer Ul-Haq (Medicinal Chemistry Research, 2020)

Biofortification with Zinc and Iron Improves the Grain Quality and Yield of Wheat Crop - Yasir Ramzan; Muhammad Bilal Hafeez; Shahbaz Khan; Majid Nadeem; Saleem-ur-Rahman; Sumaira Batool; Javed Ahmad (International Journal of Plant Production, 2020)

Systematic and paleoecological study of the new remains of Brachypotherium (Rhinocerotidae) from the Middle Miocene Siwaliks (Pakistan) - Amtur Rafeh; Abdul Majid Khan; Rana Manzoor Ahmad; Mudassar Iqbal; Muhammad Akhtar (Arabian Journal of Geosciences, 2020)

Environmental risk assessment of diclofenac residues in surface waters and wastewater: a hidden global threat to aquatic ecosystem - Hafsa Hanif; Amir Waseem; Sundas Kali; Naveeda Akhtar Qureshi; Muhammad Majid; Mazhar Iqbal; Tofeeq Ur-Rehman; Muhammad Tahir; Sohail Yousaf; Muhammad Mazhar Iqbal; Imtiaz Ahmad Khan; Mazhar Iqbal Zafar (Environmental Monitoring and Assessment, 2020)

Adaptations in Imperata cylindrica (L.) Raeusch. and Cenchrus ciliaris L. for altitude tolerance - Khawaja Shafique Ahmad; Ambreen Wazarat; Ansar Mehmood; Muhammad Sajid Aqeel Ahmad; Majid Mahmood Tahir; Fahim Nawaz; Haroon Ahmed; Mohsin Zafar; Aneela Ulfat (Biologia, 2020)

Genome wide characterization, evolution and expression analysis of FBA gene family under salt stress in Gossypium species - Muhammad Shehzad; Allah Ditta; Xiaoyan Cai; Zhongli Zhou; Xingxing Wang; Yanchao Xu; Yuqing Hou; Muhammad Yasir; Majid Khan; Kunbo Wang; Fang Liu (Biologia, 2019)

Development and Evaluation of Optimized Thiolated Chitosan Proniosomal Gel Containing Duloxetine for Intranasal Delivery - Maryam khatoon; Muhammad Farhan Sohail; Gul Shahnaz; Fiza ur Rehman; Fakhar-ud-Din; Asim ur Rehman; Naseem Ullah; Umair Amin; Gul Majid Khan; Kifayat Ullah Shah (AAPS PharmSciTech, 2019)

Cadmium (Cd) concentration in wheat (Triticum aestivum) grown in Cd-spiked soil varies with the doses and biochar feedstock - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Irfan Sohail; Amjad Hussain; Muhammad Farooq Qayyum; Hinnan Khalid; Muhammad Zeeshan; Naveeda Majid (Arabian Journal of Geosciences, 2018)

Evaluation of Ordinary Least Square (OLS) and Geographically Weighted Regression (GWR) for Water Quality Monitoring: A Case Study for the Estimation of Salinity - Majid Nazeer; Muhammad Bilal (Journal of Ocean University of China, 2018)

Plagioneurin B, a potent isolated compound induces apoptotic signalling pathways and cell cycle arrest in ovarian cancer cells - Noraziah Nordin; Nazia Abdul Majid; Rozana Othman; Fatima Abdelmutaal Ahmed Omer; Muhammad Nazil Afiq Nasharuddin; Najihah Mohd Hashim (Apoptosis, 2018)

Aminolevulinic acid and nitric oxide regulate oxidative defense and secondary metabolisms in canola (Brassica napus L.) under drought stress - Nudrat Aisha Akram; Majid Iqbal; Atta Muhammad; Muhammad Ashraf; Fahad Al-Qurainy; Sidra Shafiq (Protoplasma, 2018)

Evaluating the variability and trends in extreme climate events in the Kashmir Valley using PRECIS RCM simulations - Ishfaq Gujree; Ishfaq Wani; Muhammad Muslim; Majid Farooq; Gowhar Meraj (Modeling Earth Systems and Environment, 2017)

Satellite-based rainfall estimation and discharge measurement of Middle Indus River, Pakistan - Syed Muhammad Zubair Younis; Muhammad Majid; Ahmad Ammar (Arabian Journal of Geosciences, 2017)

Formulation and In Vitro Characterization of Thiolated Buccoadhesive Film of Fluconazole - Kiran Naz; Gul Shahnaz; Naveed Ahmed; Naveeda Akhtar Qureshi; Hafiz Shoaib Sarwar; Muhammad Imran; Gul Majid Khan (AAPS PharmSciTech, 2017)

Relationship between land use composition and PM10 concentrations in Iskandar Malaysia - Muhammad Azahar Zikri Zahari; M. Rafee Majid; Chin Siong Ho; Gakuji Kurata; Nordin Nadhirah; Safitri Zen Irina (Clean Technologies and Environmental Policy, 2016)

Mutation in SLC6A9 encoding a glycine transporter causes a novel form of non-ketotic hyperglycinemia in humans - Majid Alfadhel; Marwan Nashabat; Hanan Al Qahtani; Ahmed Alfares; Fuad Al Mutairi; Hesham Al Shaalan; Ganka V. Douglas; Klaas Wierenga; Jane Juusola; Muhammad Talal Alrifai; Stefan T. Arold; Fowzan Alkuraya; et al. (Human Genetics, 2016)

Synthesis and structural elucidation of two new series of aurone derivatives as potent inhibitors against the proliferation of human cancer cells - Aboubaker A. Elhadi; Hasnah Osman; Muhammad Adnan Iqbal; Sharmila K. Rajeswari; Mohamed B. Khadeer Ahamed; Amin M.S. Abdul Majid; Mohd Mustaqim Rosli; Ibrahim Abdul Razak; Aman Shah Abdul Majid (Medicinal Chemistry Research, 2015)

Geochemical study of the Cretaceous–Tertiary boundary succession exposed at Duhok Dam area (eastern Tethys): Northern Iraq - Muhammad S. Salih; Majid M. Al-Mutwali; Salim M. Aldabbagh (Arabian Journal of Geosciences, 2015)

Synthesis of water soluble copper(II) complexes: crystal structures, DNA binding, oxidative DNA cleavage, and in vitro anticancer studies - Tan Yi Han; Teoh Siang Guan; Muhammad Adnan Iqbal; Rosenani A. Haque; K. Sharmila Rajeswari; Mohamed B. Khadeer Ahamed; A. M. S. Abdul Majid (Medicinal Chemistry Research, 2014)

Antioxidant response of Cassia angustifolia Vahl. to oxidative stress caused by Mancozeb, a pyrethroid fungicide - Uzma Majid; Mahmooduzzafar; Tariq Omar Siddiqi; Muhammad Iqbal (Acta Physiologiae Plantarum, 2014)

Synthesis of metal(II) [M = Cu, Mn, Zn] Schiff base complexes and their Pro-apoptotic activity in liver tumor cells via caspase activation - Abeer Mohamed Farag; Teoh Siang Guan; Hasnah Osman; A. M. S. Abdul Majid; Muhammad Adnan Iqbal; Mohamed B. Khadeer Ahamed (Medicinal Chemistry Research, 2013)

Synthesis, structure, anticancer, and antioxidant activity of para-xylyl linked bis-benzimidazolium salts and respective dinuclear Ag(I) N-heterocyclic carbene complexes (Part-II) - Rosenani A. Haque; Muhammad Adnan Iqbal; Patrick Asekunowo; A. M. S. Abdul Majid; Mohamed B. Khadeer Ahamed; Muhammad Ihtisham Umar; Sawsan S. Al-Rawi; Fouad Saleih R. Al-Suede (Medicinal Chemistry Research, 2013)

Synthesis and anticancer activity of para-xylyl linked bis-benzimidazolium salts and respective Ag(I) N-heterocyclic carbene complexes - Muhammad Adnan Iqbal; Rosenani A. Haque; Mohamed B. Khadeer Ahamed; A. M. S. Abdul Majid; Sawsan S. Al-Rawi (Medicinal Chemistry Research, 2013)